Commercial Operation and Marketing Strategies of Sporting Events - Bao, Jingwen (Transactions on Economics, Business and Management Research, 2024)
As globalization continues to deepen, sporting events are not only economic competitions but also intersections of culture and commerce. The commercial operations and marketing strategies of sporting events directly affect the success of the events and can even promote the development of the sports industry and urban economies. Currently, with the increasing demand from audiences for viewing sporting events, coupled with the widespread use of new media and big data technologies, higher requirements are set for the commercial operations and marketing strategies of these events. To some extent, as bridges of cultural exchange, sporting events possess unique charm and can bring substantial economic benefits to host cities. Therefore, how to effectively manage commercial operations and develop comprehensive marketing strategies deserves significant attention. This paper aims to delve into the commercial operations and marketing strategies of sporting events, analyze the current market environment and audience demands, and propose targeted strategic recommendations to support the sustainable development of sporting events.